OphthoPods: An Analysis of the Educational Content and Changes of Ophthalmology Podcasts - Greene, Isaiah I.; Gold, Fradah E.; Tan, Nicholas E.; Fang, Alexander H.; Hodgson, Nickisa M. (Journal of Academic Ophthalmology, 2023)
Objective Podcasts are a novel modality for digitally disseminating ophthalmic knowledge, yet minimal information exists on their offerings. This study sought to describe the growth of ophthalmology podcasts, characterize their features, and analyze clinically pertinent content trends.Materials and Methods Apple Podcasts, Spotify, Google Podcasts, and Google Search were queried for English- language shows relating primarily to ophthalmology. Ninety-six podcasts and 3,594 episodes were analyzed.Results Of the 48 currently active shows, most cover general ophthalmology topics (n = 25, 52.1%) and are run by multiple hosts (n = 29, 60.4%) in both academics and private practice. The majority of podcasts released episodes monthly (n = 21, 21.9%) or less frequently than monthly (n = 36, 37.5%). Among all episodes, procedural topics (n = 951 episodes, 26.4%) and clinical education (n = 1385, 38.5%) were the most prevalent categories. Retina was the most represented subspecialty in podcast production, while oculoplastics and neuro-ophthalmology had the fewest podcasts. Episodes on disease pathophysiology (p = 0.04) and published research (p < 0.001) each declined over time. The proportion of episodes released from 2020 to 2022 that discussed digital technologies was 33.3% greater versus 2005 to 2019 (p = 0.005). Personal retrospective episodes doubled, career guidance and patient perspectives tripled, and wellness and social justice topics increased fivefold (all p < 0.001).Conclusion In summary, the coronavirus disease 2019 pandemic coincided with a rise in ophthalmology podcasts and shifts in content. Podcasts have trended toward practical advice and technologies, reflecting their value in sharing modern, peer-to-peer pearls. Emphases on storytelling and social justice offer unique, clinically relevant perspectives compared with traditional modalities.
Keywords: digital media; education; ophthalmology; podcasts